Microvascular circulatory dysregulation driven in part by cystathionine gamma‐lyase: A new paradigm for cardiovascular compromise in the preterm newborn. (30th October 2018) - Dyson, Rebecca M.; Palliser, Hannah K.; Wilding, Nicole; Kelly, Megan A.; Chwatko, Grazyna; Glowacki, Rafal; Berry, Mary J.; Ni, Xin; Wright, Ian M. R.
Abstract: Objective: H2 S may explain the dysregulation of microvascular tone associated with poor outcome following preterm birth. In adult vasculature, H2 S is predominantly produced by CSE. We hypothesized that vascular CSE activity contributes to microvascular tone regulation during circulatory transition. Methods: Preterm (GA62) and full‐term (GA69) guinea pig fetuses and neonates were studied. Microvascular blood flow was assessed by laser Doppler flowmetry. Thiosulfate, primary urinary metabolite of H2 S, was determined by high‐performance liquid chromatography. Real‐time H2 S production was assessed using a microrespiration system in fetal and postnatal (10, 24 hours) skin and heart samples. CSE contribution was investigated by inhibition via propargylglycine. Results: In preterm animals, postnatal H2 S production capacity in peripheral vasculature increased significantly and was significantly reduced by the inhibition of CSE. Urinary thiosulfate correlated with both microvascular blood flow and capacity of the vasculature to produce H2 S. H2 S produced via CSE did not correlate directly with microvascular blood flow. Conclusions: In preterm neonates, H2 S production increases during fetal‐to‐neonatal transition and CSE contribution to total H2 S increases postnatally. CSE‐dependent mechanisms may therefore underpin the increase in H2 S production over the first 72 hours of life in preterm human neonates, associated with both central and peripheral cardiovascular instability.